(untitled) (Lafia Journal of Scientific and Industrial Research, 2025)
This paper presents an improved Zeta DC-DC converter integrated with a hybrid multilevel converter topology for efficient single-phase induction motor (SPIM) control. The proposed system aims to enhance power quality, reduce total harmonic distortion (THD), and improve the dynamic performance of the motor drive. The improved Zeta converter provides a stable and regulated DC link voltage with reduced ripple, ensuring efficient power conversion and better motor control. The hybrid multilevel inverter configuration minimizes switching losses and enhances output voltage quality by generating stepped waveforms with lower harmonic content. This combination enables smooth speed control and high efficiency operation of the SPIM, making it suitable for low-power industrial and residential applications. Simulation results validate the effectiveness of the proposal topology in terms of the reduced harmonics, improved voltage regulation, and enhanced motor performance compared to conventional converter-inverter topologies.